2015
DOI: 10.1287/deca.2015.0319
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Public–Private Partnerships in Disaster Management via Centralized and Decentralized Models

Abstract: T he objective of this paper is to help both public and private sectors make better decisions in defensive resource allocation through public and private partnerships (PPPs). In this paper, efficient PPPs are studied with regard to disaster preparedness using a decentralized model (sequential game where the public sector is the first mover) and a centralized model. This paper identifies the best public investment policies by evaluating the effectiveness of incentive provisions based on the various private stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…It sometimes reveals the difficulties faced by the government in allocating available resources, 44 meaning that it fails to allocate the resources properly due to the inefficiency of the system. 44 In addition, some studies have suggested that the government's inattention to disaster management had been partially offset by greater public participation. [45][46][47] There are different studies about 3P in Iran, especially about the health sector.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It sometimes reveals the difficulties faced by the government in allocating available resources, 44 meaning that it fails to allocate the resources properly due to the inefficiency of the system. 44 In addition, some studies have suggested that the government's inattention to disaster management had been partially offset by greater public participation. [45][46][47] There are different studies about 3P in Iran, especially about the health sector.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies suggest that the contribution of communities and people in anticipating risks, limiting risk effects, and accelerating recovery after a disaster is vital. 43,44 Of course, public sectors asking for help from private sectors and for people to respond does not necessarily indicate the inability of the government or lack of resources to respond. It sometimes reveals the difficulties faced by the government in allocating available resources, 44 meaning that it fails to allocate the resources properly due to the inefficiency of the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than subsidies, they consider the effects of taxation, and note that "Taxation can…ameliorate companies' incentive to free ride on governments' provision of safety efforts" (Hausken and Zhuang, 2016). Of this work, Guan and Zhuang (2015) is closest in nature to ours, but they focus on differences in the damage levels experienced by public and private players, not differences in discount rates.…”
Section: Game Theory For Relocation and Disaster Managementmentioning
confidence: 99%
“…Theoretical and practical aspects of PPP mechanism and its role in the modernization of the economy are reflected in the works of several scientific researches (Abe, 2013;Chan, 2014;Emek, 2015;Guan, 2015;Woodson, 2015;Theodoropoulos and Tassopoulos 2014a;2014b andTkacheva et al, 2016).…”
Section: Introductionmentioning
confidence: 99%